Indian writings in English (Atlantic Publishers and Distributors, 1996)
The present volume , comprising papers by eminent scholars on different aspects of Indian English literature aims at appraising and evaluating thematic concern, formal strategies and narrative techniques, often from a comparative perspective. The writers analyzed are: Sri aurobindo, Kamala das, K. N. Daruwalla, A. K. Ramanujan, Dilip Chitre, Contemporary women poets, Margerett chatterjee, Raji narsimhan, Mulk raj anand, R. K. Narayan, Raja rao, Bhabani bhattacharya, Kamala markandeya, Anitha desai and vikram seth